(untitled) (Rainbow Journal, 2019)
Teacher can have different expection with their children to make senior in the future. This study aimed to explore primary level teachers’ expectation with their children to make secondary level mathematics teachers. A phenomenological study was conducted with primary teachers. Three public schools, one from each of Dhading, Gorkha and Kavrepalanchock district were selected conveniently. Three primary teachers respondents, one from each sample school were selected purposively. A semi-structured interview was the main method of data collection. The thematic analysis showed that primary level teachers have a common motivation of teaching their children mathematics and to make them secondary level mathematics teacher in future due to their bitter experiences of being a junior, the judgment of society toward them and leading their children a worthy life fulfilling their dreams. Further earning through tuition and other extra classes and the prestigious job is the other motivating factor to make their children secondary level mathematics teacher which brings prosperity and happiness in their life and family.